Factors Contributing to Speaking Difficulties in Young EFL Learners: An Exploratory Study - Saragih, Ibnu Ziat; Kembaren, Farida Repelita Waty; Saragih, M Afiv Toni Suhendra (English Teaching and Linguistics Journal (ETLiJ), 2024)
Many English as a Foreign Language (EFL) learners, especially young beginning-level students with limited exposure to English, struggle to speak the language fluently. However, research specifically examining the obstacles to speaking skill development among young EFL learners is lacking, particularly in regions where English has no official status. This study explored Indonesia EFL teachers' perceptions of factors contributing to early primary school students' difficulties with spoken English. The goal was to establish a foundation for further research and pedagogical improvements.  A questionnaire with Likert-scale ratings and open-ended questions was given to 194 teachers from 70 Indonesia public and private primary schools. Quantitative and qualitative analyses identified patterns and rationales in the teachers' judgments of sources of students' speaking struggles. Pronunciation, vocabulary gaps, grammar, lack of practice, and anxiety were most frequently cited as moderate to substantial challenges. Teaching experience and school type influenced perceptions of anxiety's role and scaffolding orientations. The findings offer initial insight into context-specific developmental and environmental constraints on young Indonesia learners' progress in speaking English. Future targeted research can build on this exploratory platform to inform responsive instructional interventions during this critical period of language acquisition